Crystallization of lisoleucine with the influence of electric field / Umi Rafiah Shukri - Shukri, Umi Rafiah (2015)
Problems encountered in crystallization when the end-product does not meet particular requirement for industry specifically in pharmaceutical and fine chemical production.Good quality crystals are defined as crystals with uniform size, shape and correct polymorphic form. Various methods have been established in attempt to achieve the good quality crystal by enhancing the metastable zone width region with external influence. Electric field was chosen in this study to solve the issues. In this study,Lisoleucine was the main material used meanwhile glycine is the other material due to the interesting characteristic of amino acids to exist as zwitterions in solution.Mechanism of this work is known as effect of electric field in crystallization.Investigations of this study focus on speciation behaviour of L-isoleucine in solution and crystallization of the amino acid in distilled water, acidic and basic solutions with the presence of electric field for selected temperatures; 10, 25, 40, 55 and 70°C. From speciation analysis, it is observed that the pKa values increases with the increases of applied electric field demonstrating obstacles added to the system to dissociate H+ from both -COOH and -NH3+. Crystallization of L-isoleucine in distilled water in the presence of electric field depicted the presence of new phase of the crystal structure proven by XRPD with consistent new peak at 20 of 31.0°. This result was supported by thermal properties of DSC data showing the presence of new melting temperature at 380°C. Findings from FTIR proved no proton transfer occurrence when crystallization is induced by electric field. Crystallization of glycine in distilled water with the influence of electric field demonstrates no change of polymorphic form proven by XRPD, DSC and FTIR data. Influence of pH condition in the presence of electric field demonstrated changes in L-isoleucine morphologies as well as the crystals properties.